Orbitofrontal Reality Filtering - Schnider, Armin (Frontiers in Behavioral Neuroscience, 2013)
Decades of research have deepened our understanding of how the brain forms memories and uses them to build our mental past and future. But how does it determine whether an evoked memory refers to the present and can be acted upon? The study of patients who confuse reality, as evident from confabulation and disorientation, has opened ways to explore this vital capacity. Results indicate that the brain recurs to a phylogenetically old faculty of the orbitofrontal cortex –extinction– and structures of the reward system to keep thought and behavior in phase with reality.